Kinase-Based Taming of Brain Microglia Toward Disease-Modifying Therapy - Lee, Sun-Hwa; Suk, Kyoungho (Frontiers in Cellular Neuroscience, 2018)
Microglia, the brain’s resident immune cells, play crucial roles in the health and disease of the central nervous system (CNS). Depending on the CNS inflammatory milieu, they exist in either resting or activated states. Chronic neuroinflammation mediated by activated microglia is now considered to be a common characteristic shared by many neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis, which currently pose a considerable social and economic burden to the global healthcare system. Accumulating evidence has indicated protein kinases as important drug targets in the development of therapeutic alternatives for the treatment of these detrimental diseases. Here, we review recent findings suggesting that selected protein kinases potentially participate in microglia-mediated neuroinflammation. Taming microglial phenotypes by modulating the activity of these protein kinases holds great promise for the development of disease-modifying treatments for many neurodegenerative diseases.